3a + 2a = 5a
2a + 3a = 5a
5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)
2a - 5a = -3a
(5a+8) - (2a+4) =3a +4 To do this, simply subtract like terms. 5a-2a=3a and 8-4=4
If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1
2a² + 6a
2a + 3a + 4 = 5a + 4
-2a plus 3b
2a + 4b
5a + 11
Gathering like terms together, this is equal to 5a + 3b + 7c.
(2a - 1)(3a + 4)
The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.
3a x 2a =24
Added together they equal 8a
a is equal to 4
5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4
A, 2A, 3A, 4A, 5A, and so on.
The given expression can be simplified to: 3b-a
2a+5a+9a = 16a
6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b